MENGEMBANGKAN KOMPETENSI PEDAGOGIK GURU PAI SD/MI DENGAN MODEL PEMBELAJARAN KOOPERATIF - Rofiah, Nurul Hidayati (Dinamika, 2014)
Teacherâs pedagogical competence can be developed and the quality can be increasedthrough the application of cooperative learning model. By using this model, a teachercould use many interesting methods to improve the studentsâ interest, motivation andachievement. By this strategy, the learning interaction will be more âmany-directionâand learning source diversification. The cooperative learning strategy was directed todevelop the studentsâ cognitive ability as well as their interpersonal competence.Cooperative learning strategy is one of the alternatives can be used in Islamic Educationfor effective and efficient learning to achieve the determined learning goals.Cooperative learning strategy is psychologically suitable with the studentsâ socialdevelopment in their age of SD/MI and suitable with their characteristic that is to enjoyworking in groups. Cooperative learning strategy is also a reflection of the Indonesiancharacter namely mutual cooperation. Therefore, the learning should be suitable withthe society condition and the mutual cooperation should be the principle coloring thislearning practice for the students. In the application of cooperative learning, it needs thewillingness and the ability as well as the teachersâ creativity to manage class, so theteacher will be more active especially in making well-done lesson plans, classmanagement in action, and make assignment for students with groups.Keywords: Pedagogical Competence, Cooperative Learning Model, Islamic Educationin SD/MI